Neural depolarization triggers Mg2+ influx in rat hippocampal neurons. (3rd December 2015) - Yamanaka, R.; Shindo, Y.; Karube, T.; Hotta, K.; Suzuki, K.; Oka, K.
Highlights: Depolarization-induced Mg 2+ influx. No correlation between the amplitudes of Mg 2+ and Ca 2+ responses. Mg 2+ mobilizations mediated by 2-APB-sensitive channels. Abstract: Homeostasis of magnesium ion (Mg 2+ ) plays key roles in healthy neuronal functions, and deficiency of Mg 2+ is involved in various neuronal diseases. In neurons, we have reported that excitotoxicity induced by excitatory neurotransmitter glutamate increases intracellular Mg 2+ concentration ([Mg 2+ ]i ). However, it has not been revealed whether neuronal activity under physiological condition modulates [Mg 2+ ]i . The aim of this study is to explore the direct relationship between neural activity and [Mg 2+ ]i dynamics. In rat primary-dissociated hippocampal neurons, the [Mg 2+ ]i and [Ca 2+ ]i dynamics were simultaneously visualized with a highly selective fluorescent Mg 2+ probe, KMG-104, and a fluorescent Ca 2+ probe, Fura Red, respectively. [Mg 2+ ]i increase concomitant with neural activity by direct current stimulation was observed in neurons plated on an indium-tin oxide (ITO) glass electrode, which enables fluorescent imaging during neural stimulation. The neural activity-dependent [Mg 2+ ]i increase was also detected in neurons whose excitability was enhanced by the treatment of a voltage-gated K + channel blocker, tetraethylammonium (TEA) at the timings of spontaneous Ca 2+ increase. Furthermore, the [Mg 2+ ]i increase was abolished in Mg 2+ -free extracellular medium, indicating [Mg 2+ ]i increase is due to Mg 2+ influx induced by neural activity. The direct neuronal depolarization by veratridine, a Na + channel opener, induced [Mg 2+ ]i increase, and this [Mg 2+ ]i increase was suppressed by the pretreatment of a non-specific Mg 2+ channel inhibitor, 2-aminoethoxydiphenyl borate (2-APB). Overall, activity-dependent [Mg 2+ ]i increase results from Mg 2+ influx through 2-APB-sensitive channels in rat hippocampal neurons.